BST405 – Conservation and Management of Natural Resources (Pemuliharaan dan Pengurusan Sumber Asli) - February - March 2022 - PPSKJ, Pusat Pengajian Sains Kajihayat (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 BST405 – Conservation and Management of Natural Resources (Pemuliharaan dan Pengurusan Sumber Asli) Duration : 2 hours (Masa : 2 jam)